Необходимые и достаточные условия мгновенной компактификации носителя решения и двусторонние оценки его размеров в задаче Коши для параболического уравнения с двойной нелинейностью и абсорбцией - Дегтярев, С.П. (Видавничий дім "Академперіодика" НАН України, 2007)
We study the instantaneous support shrinking phenomenon for a doubly nonlinear degenerate
parabolic equation in the case of slow diffusion, when the initial Cauchy data are, in general,
Radon measures. For nonnegative solutions, we obtain the necessary and sufficient conditions for the instantaneous support shrinking phenomenon in terms of local behavior of the array of the initial data and, in the same terms, we express the bilateral estimates exact with respect to order for the support size.